Identificación de Clostridium perfringens en carne de cerdo hornada expendida en los mercados de la ciudad de Azogues. - Cárdenas Palomeque, Diana Carolina (2025)
Food safety is a fundamental aspect of public health, particularly in local markets where meat products are sold, as these types of prepared foods can cause serious illnesses in consumers. This underscores the importance of implementing appropriate hygiene and sanitary controls. Therefore, this study aimed to determine the presence of C. perfrigens in roasted pork sold in these markets. The research used an observational, descriptive, and cross-sectional design, with a 100% sample of the vendor population (n=30). Samples of roasted pork were taken at different times and analyzed at the Biotechnology Center of the National University of Loja (UNL, for its Spanish acronym) following the INEN 1529.18:2013 standard. The results showed that no presence of C. perfrigens was detected in any of the samples; however, other microorganisms such as Salmonella spp., Escherichia colt, and Stapkylococcus aureus were identified, highlighting the need to improve hygienic practices at the market stalls. Risk factors associated with contamination were evaluated, identifying the main issues as the inadequate separation of raw and cooked foods, the failure to use separate utensils for preparation and sale, and improper waste management. These deficiencies in vendors' hygiene practices and the management of the market stalls pose a sigliificant risk to food safety.